Role of physical activity in cardiovascular disease prevention: impact of epigenetic modifications - Yi Sun; Zuoying Peng; Hua Liang (Frontiers in Cardiovascular Medicine)
Cardiovascular disease (CVD) remains the leading cause of death worldwide, imposing a major burden on morbidity, quality of life, and societal costs, making prevention of CVD a top public health priority. Extensive research has pointed out that lack of adequate physical activity in life is one of the key risk factors for heart disease. Indeed, moderate exercise is not only beneficial to the heart in healthy populations, but also exerts a protective effect in pathological states. However, the molecular mechanisms underlying the cardioprotective effects of exercise are still not fully understood. An increasing body of research indicates that variations in the epigenetic system—such as DNA methylation, histone modifications, and production of non-coding RNA—are essential for maintaining heart health and preventing heart disease. Exercise is a potent epigenetic modulator that induces direct and long-lasting genetic changes and activates biological signals associated with cardiovascular health. These changes can be influenced by external stimuli such as physical activity and may even be passed on to offspring, thus providing a mechanism for generating genetic effects through behavioral interventions. Therefore, understanding this relationship can help identify potential biomarkers and therapeutic targets associated with CVD. This study aims to provide an overview of the beneficial effects of exercise on heart health. This information may help guide future research efforts and improve our understanding of epigenetics as a therapeutic, prognostic, and diagnostic biomarker for CVD.